Design of a Melinjo Flaking Machine with Hopper and Semi Automatic Collecting Tray - Miftahurrahman Miftahurrahman; Ahmad Akromul Huda; Karyanik Karyanik; Sirajuddin H. Abdullah (Universitas Muhammadiyah Mataram, 2024)
Demand for melinjo chips is high, but the current production method is less efficient in terms of time. The melinjo flattening machine is a new innovation that has the potential to replace the conventional process, thus optimising post-harvest handling. It is expected that the use of this flattening machine can increase work capacity and facilitate the production of quality melinjo flattening products in the future. This study used experimental methodology with a one-factor completely randomised design (CRD) research design. The experiment consisted of three treatments, namely P1, P2, and P3, with amounts of 1000 grams, 2000 grams, and 3000 grams, respectively. Each treatment was repeated three times, resulting in nine experimental units. Observation data were analysed using the BNJ test at the 5% level to determine which treatment had a significant effect on yield. The test results show that the melinjo seed flattener can operate properly. In testing the capacity of the tool shows the greatest working capacity of the machine, P3, which is 28.73 grams/minute. The processing time test shows that the treatment that produces the most time is P3 of 88 minutes. In testing the weight of the flattener results show that P3 produces the most with a value of 2516.67 grams. It is necessary to make improvements to the hopper and redesign by calculating the bulk angle of melinjo seeds, so that melinjo seeds can easily go down to the rationing section. In addition, a stirrer is designed for melinjo seeds that are ready to be flaked with the flattening machine so that when roasting with a stirrer, the melinjo seeds that are still hot are immediately put into the hopper so that they can be flattened using the semi-automatic flattening machine.